Elevated levels of protein AMBP in cerebrospinal fluid of women with preeclampsia compared to normotensive pregnant women. Issue 1 (24th October 2016) - van den Berg, Caroline B.; Duvekot, Johannes J.; Güzel, Coşkun; Hansson, Stefan R.; de Leeuw, Thomas G.; Steegers, Eric A. P.; Versendaal, Johannes; Luider, Theo M.; Stoop, Marcel P.
Abstract : Purpose: To investigate the cerebrospinal fluid (CSF) proteome of patients with preeclampsia (PE) and normotensive pregnant women, in order to provide a better understanding of brain involvement in PE. Experimental design: Ninety‐eight CSF samples (43 women with PE and 55 normotensive controls) were analyzed by LC–MS/MS proteome profiling. CSF was obtained during the spinal puncture before caesarean delivery. Results: Eight proteins were higher abundant and 17 proteins were lower abundant in patients with PE. The most significantly differentially abundant protein was protein AMBP (alpha‐1‐microglobulin/bikunin precursor). This finding was validated by performing an ELISA experiment ( p = 0.002). Conclusions and clinical relevance: The current study showed a clear difference between the protein profiles of CSF from patients with PE and normotensive pregnant women. Protein AMBP is a precursor of a heme‐binding protein that counteracts the damaging effects of free hemoglobin, which may be related to the presence of free hemoglobin in CSF. Protein levels showed correlations with clinical symptoms during pregnancy and postpartum. To our knowledge, this is the first LC–MS/MS proteome profiling study on a unique set of CSF samples from (severe) preeclamptic patients and normotensive pregnant women.